Strategi Komunikasi Pemasaran Digital Bening's Clinic Dalam Meningkatkan Loyalitas Pelanggan Melalui Akun Instagram - Mustika, Pina; Dana, Vabrian Prima; Sukma, Agus Hitopa; Marzuku, Alamsyah (Prisani Cendekia Institute, 2025)
This study aims to identify and analyze the digital marketing communication strategies employed by Bening's Clinic in an effort to increase customer loyalty through its Instagram account. Consumer loyalty plays an important role in a company; retaining consumers means improving performance and maintaining the company's survival, which is the main reason for a company to attract and retain consumers. The research method used is a qualitative approach with in-depth interviews with Bening's Clinic management and consumers, as well as documentation. The results show that Bening's Clinic's digital marketing communication strategy through Instagram is effective in increasing customer loyalty. The clinic has succeeded in strengthening its relationship with customers through consistent and interesting content, such as education, testimonials, and relevant promotions. Despite facing challenges such as changes in Instagram's algorithm and fierce competition, Bening's Clinic was able to overcome these obstacles by conducting regular evaluations and innovating in content presentation. With an adaptive and interactive approach, Bening's Clinic's digital strategy succeeded in building trust and encouraging customers to continue using its services.